Efficacy of floral preservatives stored at different temperatures and time periods on lushness retention and vaselife of chrysanthemum (Dendranthema × grandiflora) cv. Thai Chen Queen - JAIN, RITU; JANAKIRAM, T; KUMAWAT, G L (The Indian Journal of Agricultural Sciences, 2016)
Different floral preservative treatments consisting of citric acid, 8HQ, sucrose and their combinations stored at different temperatures and duration (time periods) were used to reduce the foliage discoloration and to enhance the vase life of chrysanthemum (Dendranthema × grandiflora Ramat.) cv. Thai Chen Queen, at ICAR-IARI, New Delhi during 2012-14. Experiment was laid out in completely randomized block design with sixteen treatments and three replications. It was observed that all the preservative treatments significantly reduced foliage discoloration and increased the vase life over control (Distilled water). The preservative solution containing 400 ppm 8HQ+400 ppm citric acid+ 3% sucrose +one year old storage at low temperature (T14) resulted in maximum vase life (36.56 days), maximum chlorophyll content with zero wilting and leaf yellowing and reduced leaf browning. Minimum weight loss (9.48%) was recorded in 400ppm 8HQ+400ppm citric acid +3 month old storage at low temperature (T5). However, maximum volume of solution consumed (104.72 ml) was recorded in 400 ppm 8HQ+400 ppm citric acid+3% sucrose+6 month old storage at low temperature (T10), whereas maximum flower diameter (12.37cm) was recorded in 400ppm 8HQ+400 ppm citric acid+3% sucrose+3 month old storage at low temperature (T6).